Pembelajaran Matematika Berbasis E-learning untuk Meningkatkan Literasi Matematis Siswa (UIN Sunan Gunung Djati Bandung, 2025)
Mathematics learning is developing rapidly in today's era. E-learning is a tool in mathematics learningto improve mathematical literacy. The purpose of this study was to determine e-learning-basedmathematics learning in improving mathematical literacy. The method used is a systematic reviewof literature. The results of research related to e-learning-based mathematics learning to improvestudents' mathematical literacy have received quite good attention in recent years, as shown by theincreasing number of researchers who review research related to the application of e-learning toimprove mathematical literacy in 2020-2024. Second, research tends to be conducted at the juniorhigh school level with the most commonly chosen material being trigonometry, statistics, andquadrilaterals. Third, this literature review is dominated by Java and Bali by choosing quantitativeresearch as its research method. Fourth, the most widely used learning model is the blended learningmodel, while the most widely chosen e-learning media is the Google Classroom application. Fifth, elearning-based mathematics learning is effective in improving students' mathematical literacy inIndonesia. The benefit of this study is that readers gain useful insight or knowledge. Suggestions forother researchers are hopefully able to conduct research throughout Indonesia.